A Book Review on Montanari and Quay’s (Eds.) Multidisciplinary Perspective on Multilingualism: The Fundamentals - Feisal Aziez (University of Muhammadiyah Purwokerto, 2020)
The volume provides a comprehensive and multidimensional discussion of multilingualism from a broader framework i.e. sociolinguistic perspective, to a more individual i.e. psycholinguistic perspective, and eventually to a more detailed point of view i.e. neurolinguistics perspective. The chapters in the volume is categorized thematically into four separate parts which make it easier for readers to navigate through the general idea of the volume. The recent and relevant issues in the volume makes it a valuable reading for practitioners and especially researchers wanting to reflect on the practices of multilingualism and use it as a reference for future studies. This volume is also an essential resource for graduate students interested in the field. Nevertheless, another volume following the current one is something to look forward to in order to fill the gaps in terms of updates on the practices of multilingualism especially in the countries or regions not included in this volume. At the moment, on the whole, this volume is a rich and comprehensive resource especially for those interested in the topic of multilingualism.